TECHNOLOGIES FOR THE DEVELOPMENT OF ENTREPRENEURIAL COMPENSATION IN STUDENTS ON THE BASE OF VITAGEN EXPERIENCE - Pirniyazova Malika Kenesbaevna; Nosirov Sayfiddin Salohiddin og’li (Western European Studies, 2024)
In the article, the process of developing entrepreneurship skills in students based on vitagen experience is diagnostic. Therefore, it is necessary to determine and assess the level of students' vitagen experience, which is the basis for the development of entrepreneurial skills. This process was organized on the basis of engaging students to complete tests and tasks related to the field. Tests were brought to the attention of the respondent-students, which will help to determine whether they have entrepreneurial competencies and vitagen experience that will be the basis for the development of these competencies. This is what the article talks about.
Keywords: entrepreneurial competences; vitagen experience; test